The Prediction of Prolificacy Using Linear Body Parameters and Craniometric Analysis in Etawah-Grade Does - Mulyono, R. H.; Sumantri, C.; Noor, R. R.; Jakaria, Jakaria; Astuti, D. A. (Tropical Animal Science Journal, 2018)
Etawah-grade goat is a graded  up line between Kacang and Etawah goats, which  well adapted to Indonesia’s humid tropical climate. In order to fulfill national meat requirement, it is necessary to increase the  population by increasing prolificacy. This study was aimed to determine whether the body and head measurements of the Etawah-grade does can be used as selection criteria for  indirect selection of the litter size. The use of does at 3-4 years old (I3 dental condition) from BPTU-HPT Pelaihari and Cordero farms (51 and 55 does, respectively) were based on their specific geographical location  characteristics. The body variables were withers height, hip height, body length, chest width, chest depth, thurl width, rump length, chest girth, and cannon circumference, whereas for head variables were acrocranion–prosthion, basion–prosthion, lower jaw length, head height, tuber facial left-right, nasion–rhinion, entorbitale left-right, euryon left-right, supraorbitale left-right. Bergmann methods  were applied for measuring the differences of body and head parameters followed by the principal component, Fisher’s discriminant, and principal component regression analyzes. All regression coefficients of linear body measurementss were highly correlated to the litter size (P